Upaya Membangun Keluarga Sakinah - Muhammad Dlaifurrahman (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The shekinah family is a dream for every person who builds a household mahligai. Besides that, the purpose of marriage in the teachings of Islam is to create a family that is peaceful, happy, peaceful, and prosperous. People who want to have a family must be directly and psychologically because marriage is a game but the sincerity of men or women to live a family in achieving the goals of marriage. Before having a family, the first man or woman who did that chose first to choose a life partner with wisdom that had been taught by the Prophet. The Messenger of Allah taught to look for religious factors because that would determine the happiness and peace of the household because the good religion must obey Allah and the Messenger of Allah. There are two formulas in building a sakinah family, namely the rights and obligations of the husband and family who establish good communication so that a happy family is created.